Solve this equation 13(y+7)=3(y−1)
2 answers:
Answer:
y=-9.4
Step-by-step explanation:
We will have to start solving by dealing with the bracket
13(y+7)=3(y-1)
Ok let's get to work
13y+91=3y-3
Let's collect like terms
13y-3y=-3-91
10y=-94
Let's make y the subject of formula by dividing both sides by 10
y=-9.4
Therefore the final answer is-9.4
Hope you understand how we got our final answer
13(y+7)=3(y-1)
13y+91=3y-3
13y-3y=-91-3
10y=-94
-94/10
Y=-9.4
You might be interested in
Answer:
5
Step-by-step explanation:
64 = 4 + 12g
64 - 4 = 12g
60 = 12g
60 / 12 = g
5 = g
g = 5
Answer:
3
Step-by-step explanation:
12
Answer:
b
Step-by-step explanation:
g
She has $18.50 so she needs $39.50.
6.50×3= 19.50
18.50+19.50= 38
5.25×4=21
38+21=59
Maya would have enough money to go on the trip.